Artificial Intelligence and the management of the University curriculum by competencies (La Inteligencia artificial y la gestión del currículo Universitario por competencias): e-2312: https://doi.org/10.5281/zenodo.13738948; Ref.[78%>(2018); (2019)>PFI] - Moreno Muro, Juan Pablo; Caján Villanueva , Marina; Chavez Taipe, Ysabel Victoria; Hernández Torres, Alex Miguel; Ramos León, Loida Leny; Zapata Bellido, Mickelly Julissa (GESTIONES, 2023)
Artificial intelligence (AI) can transform university curriculum management by competencies by automating the organization, search and filtering of educational resources. The resources provided by AI offer personalized content recommendations, facilitating more efficient management for students and teachers. Qualitative research, based on a review of ten reference sources and expert discussions, highlighted the importance of learning personalization, educational quality improvement, sociocultural adaptation and active student participation. The results determined that the integration of AI can improve curricular programming by offering personalization and continuous assessment, as long as it is aligned with these principles. In conclusion, AI can enrich university education by making it more dynamic and adapted to individual and collective needs, facilitating more effective training for today's work environment. Referencias Angulo , R. (2017). Knowledge Management and Organizational Learning: A Comprehensive Vision. Psychological Reports (Gestión del Conocimiento y Aprendizaje Organizacional: una Visión Integral. Informes Psicológicos,) 1(17), 53-70. Retrieved from http://dx.doi.org/10.18566/infpsic.v17n1a03 Andrade, H. (2019). A Critical Research Review​ on Student Self-Assessment . Frontiers in Education , 4(87). https://doi.org/10.3389/feduc.2019.00087 Bailey, J., Rodríguez, M.G., Flores, M., & González, P.E. (2017). Contradictions and proposals for education in the knowledge society. Sophia (Contradicciones y propuestas para la educación en la sociedad del conocimiento. Sophia) 13(2), 30-39. Barba-Martín, RA, Bores-García, D., González-Calvo, G., & Hortigüela , D. (2020). Formative assessment with student interns to reduce the theory-practice gap in initial teacher training. Physical Education and Sport, 39(1). http://doi.org/10.17533/udea.efyd.v39n1a02 Caján Villanueva, M., Calderón Torres , N. A., & Administrador. (2021). Metadata, health system and pension regimes of Peruvian artists in the context of Covid-19: Metadata, health system and pension regimes of Peruvian artists. GESTIONES (Los Metadatos, sistema de salud y regímenes pensionarios de artistas peruanos en el contexto del Covid-19: Metadatos, sistema de salud y regímenes pensionarios de artistas peruanos), 1–9. Recuperado a partir de https://gestiones.pe/index.php/revista/article/view/GESTIONES 1(1),1-9. Fernández, VHR (2021). Administrative management and teaching practice in a public educational institution. GESTIONES (La Gestión administrativa y práctica docente en una Institución Educativa pública. GESTIONES), 1 (1). Garay Paucar, E. Z., Chávez Taipe , Y. V., & Atachao Mallqui, J. C. (2022). Execution of public works and results-based management in a Peruvian regional government (Ejecución de obras públicas y gestión por resultados en un Gobierno regional del Perú): ID de ubicación: e-22.55.02; Publicado: 2022-01-27; Referencias (Hasta 5 años <2022): 56%. GESTIONES, 2(1), 1–9. Recuperado a partir de https://gestiones.pe/index.php/revista/article/view/55 Garcia , H. (2021). A school management model multigrade analysis​ public schools in san ignacio , peru . EDUCATION MAGAZINE, 45(2), 117-131. https://acortar.link/yyGGgX Gimeno, J., Feito , R., Perrenound , P. & Clemente, M. (2012). Curriculum Design, Development and Innovation . Madrid: Morata. (Diseño, Desarrollo e Innovación del Curriculum. Madrid: Morata) Jiménez, D., Gonzáles, J.J. and Tornel , M. (2020). Active methodologies in the university and their relationship with teaching approaches. Profesorado: Journal of Curriculum and Teacher Training, 24(1), 76-94. Last visit June 3, 2020. Retrieved from Retrieved from(Metodologías activas en la universidad y su relación con los enfoques de enseñanza. Profesorado: Revista de Currículum y Formación del Profesorado, 24(1), 76-94. https://digibug.ugr.es/bitstream/handle/10481/60686/8173-38599-4-PB.pdf?sequence=1&isAllowed=y Kolbe , L. (2019). School health as a strategy to improve both public health and education . Annual review of public health , 40(1), 443-463. https://doi.org/10.1146/annurev-publhealth-040218-043727 Kruger , J., Beckmann , J., and Du Plessis , A. (2022). The management and governance conundrum in South Africa public schools : Principals ' perspectives . Perspectives in Education , 40 (4), 312-324. Education Source . https://doi.org/10.38140/pie.v40i4.5735 Lazos, L., & Olivé , L. (2016). Towards an Intercultural Model of Knowledge Society in Mexico. Trilogy: Science, Technology and Society (Hacia un Modelo Intercultural de Sociedad del Conocimiento en México.Trilogía: Ciencia, Tecnología y Sociedad) 8(15),151 – 155 Luckin , R., Holmes, W., Griffiths , M. & Forcier , L.B. (2016). Intelligence Unleashed : An argument for AI in Education . Pearson. https://www.pearson. com / content / dam / one-dot-com / one-dot-com /global/ Files/ about-pearson / innovation /open-ideas/ Intelligence - Unleashed-v15-Web.Pdf Malpaso, RC, & Lapa, G. (2022). Strategic quality educational management in a Public IE in Ancash. Horizontes. Journal of Research in Educational Sciences (Gestión educativa estratégica de calidad en una I.E. Pública de Ancash. Horizontes. Revista de Investigación en Ciencias de la Educación) 6(25), 1742-1758. https://doi.org/10.33996 / revistahorizontes.v 6i25.450 Miao , F., Holmes, W., Ronghuai H., & Hui Z. (2001). Artificial intelligence and education: a guide for policy makers. https://unesdoc.unesco.org/ark:/48223/pf0000379376 Mousa , M., Massoud , H., and Ayoubi , R. (2022). Responsible management education in time of crisis: A conceptual framework for public business schools in egypt and similar middle eastern context . Public Organization Review , 22(2), 403-419. Business Source Complete. https://doi.org/10.1007/s11115-021-00532-6 Naidoo , P. (2019). Perceptions of teachers and school management teams of the leadership roles of public school main . South African Journal of Education , 39 (2), 1-14. Education Source . https://doi.org/10.15700/saje.v39n2a1534 Negre , F., Marín, V. and Pérez, A. (2018). Information Competence as a Requirement for 21st Century Teacher Training: Analysis of Didactic Strategies for its Acquisition. Profesorado: Journal of curriculum and teacher training, 22(1), 277-300. (La Competencia Informacional como Requisito para la Formación de Docente del Siglo XXI: Análisis de Estrategias Didácticas para su Adquisición. Profesorado: Revista de currículum y formación del profesorado, 22(1), 277-300. Retrieved from Retrieved from http://revistaseug.ugr.es/index.php/profesorado/article/download/9929/8052 Nieto-Rivas, E.A., Fermín, F.A., Arieta, Y.M., Mondragón, D.G., Atanacio , L., & Meneses, J. A. (2021). Experiences of managerial leadership in times of covid-19: Experiences of managerial leadership in times of covid-19: leadership in times of covid-19. South Florida Journal of Development (Experiencias del liderazgo directivo en tiempos de covid-19: Experiences of managerial leadership in times of covid-19. South Florida Journal of Development) 2(4), 6 228-6 245.https://doi.org/10.46932/sfjdv2n4-095 Orihuela, MD, Menacho , I., Mauricio, RM, & Camarena, JL (2021). Managerial competencies in teacher change management in local management unit 01, Peru. Horizontes. Journal of Research in Educational Sciences (Competencias gerenciales en la gestión del cambio de docentes en la unidad de gestión local 01, Perú. Horizontes. Revista de Investigación en Ciencias de la Educación) 5 (19), 86 3-871. https://doi.org/10.33996/revistahorizontes.v5i19.243 Öz , Ö., and Arastaman , G. (2022). school main opinions​ on data- based school management : A case study . Participatory Educational Research , 9(3), 132-147. Scopus . https://doi.org/10.17275/per.22.58.9.3 Pérez, MR, Gómez, JJ, Tamayo, O., Iparraguirre, AE, Besteiro , ED, Pérez, MR, Gómez, JJ, Tamayo, O., Iparraguirre, AE, and Besteiro , ED (2020). Psychological alterations in medical students during active research for COVID-19. MEDISAN (Alteraciones psicológicas en estudiantes de medicina durante la pesquisa activa de la COVID-19. MEDISAN)24(4), 537-548. https://acortar.link/1oy9iB Ramos Quispe, R. L. (2022). Proposal of a questionnaire on work performance and human interrelations administered by university managers (Propuesta de cuestionario sobre desempeño laboral e interrelaciones humanas administrado por directivos de Universidad): ID de ubicación: e-22.09.06; Publicado: 2022-08-08; Referencias (Hasta 5 años <2022): 68%. GESTIONES, 2(1), 1–10. Recuperado a partir de https://gestiones.pe/index.php/revista/article/view/9 Rodriguez - Gallego , MR, Ordonez -Sierra, R., and Lopez -Martínez, A. (2020). School management : Pedagogical leadership and school improvement . Journal of Educational Research , 38(1), 275-292. https://doi.org/10.6018/rie.364581 Ruesta, RG, Gejaño , CV, and Vega, CS (2022). Management and community work during the COVID-19 health emergency. Horizontes. Journal of Research in Educational Sciences (Gestión directiva y el trabajo con la comunidad durante la emergencia sanitaria por el COVID-19. Horizontes. Revista de Investigación en Ciencias de la Educación) 6 (22), 83-91. https://acortar.link/dAy6RS Sánchez, R.M., Recalde-Esnoz , I., and Ferrández , D. (2022). Challenges for school management teams in times of pandemic covid-19. International and Multidisciplinary Journal of Social Sciences , 11(3), 1-26. https://doi.org/10.17583/rimcis.10793 Tintoré , M., Gairín , J., Cabral, I., Matías, J., and Serrão , R. ( 2022). Management model , leadership and autonomy in Portuguese and Spanish public schools : A comparative analysis . Cogent Education , 9(1), 2105553. https://acortar.link/xW4wFp Tsang, K.K., Teng , Y., Lian , Y., and Wang, L. (2021). school management culture, emotional labor, and teacher burnout in mainland China. Sustainability ( Switzerland ), 13(16). Scopus . https://doi.org/10.3390/su1316 9141